5-Aryl-1,3,4-oxadiazol-2-amines Decorated with Long Alkyl and Their Analogues: Synthesis, Acetyl- and Butyrylcholinesterase Inhibition and Docking Study - Pflegr, Vaclav; Štěpánková, Šárka; Svrčková, Katarína; Svarcova, Marketa; Vinsova, Jarmila; Kratky, Martin (MDPI, 2022)
2,5-Disubstituted 1,3,4-oxadiazoles are privileged versatile scaffolds in medicinal chemistry that have exhibited diverse biological activities. Acetyl- (AChE) and butyrylcholinesterase (BChE) inhibitors are used, e.g., to treat dementias and myasthenia gravis. 5-Aryl-1,3,4-oxadiazoles decorated with dodecyl linked via nitrogen, sulfur or directly to this heterocycle have been designed as potential inhibitors of AChE and BChE. They were prepared from commercially available or in-house prepared hydrazides by reaction with dodecyl isocyanate to form hydrazine-1-carboxamides 2 (yields 67-98%) followed by cyclization using p-toluenesulfonyl chloride and triethylamine in 41-100% yields. Thiadiazole isostere was also synthesized. The derivatives were screened for inhibition of AChE and BChE using Ellman's spectrophotometric method. The compounds showed a moderate dual inhibition with IC50 values of 12.8-99.2 for AChE and from 53.1 mu M for BChE. All the heterocycles were more efficient inhibitors of AChE. The most potent inhibitor, N-dodecyl-5-(pyridin-4-yl)-1,3,4-thiadiazol-2-amine 3t, was subjected to advanced reversibility and type of inhibition evaluation. Structure-activity relationships were identified. Many oxadiazoles showed lower IC50 values against AChE than established drug rivastigmine. According to molecular docking, the compounds interact non-covalently with AChE and BChE and block entry into enzyme gorge and catalytic site, respectively.
5-Aryl-1,3,4-oxadiazol-2-aminy zdobené dlouhým alkylem a jejich analogy: Syntéza, inhibice acetyl- a butyrylcholinesterázy a studie dokování
Keywords: 1,3,4-oxadiazole; 1,3,4-thiadiazole; acetylcholinesterase; butyrylcholinesterase; enzyme inhibition; molecular docking; 1,3,4-oxadiazol; 1,3,4-thiadiazol; acetylcholinesteráza, butyrylcholinesteráza; inhibice enzymu; molekulové dokování